Willingness to Pay for Healthy Housing During the COVID-19 Pandemic in China: Evidence From Eye-Tracking Experiment - Guo, Xiaotong; Fan, Zhaoyang; Zhu, Hong; Chen, Xiangyang; Wang, Mengmeng; Fu, Hanliang (Frontiers in Public Health, 2022)
Healthy housing can set its occupants completely in good physical, mental and social conditions, but there is a lack of research in China on the public’s willingness to pay (WTP) for healthy housing. From the perspective of cognitive psychology, this study constructs an analytical framework based on the model of “theory of planned behavior” (TPB), the theory of selective information exposure, and the model of “emotions as social information”, while exploring the effect mechanism of the online reviews on the public’s WTP for healthy housing during COVID-19 pandemic. In combination with eye-tracking experiments and subjective reports, physiological, psychological and behavioral multimodal data on WTP of 65 participants for healthy housing are collected. Partial least squares structural equation modeling (PLS-SEM) is adopted to analyze the formation effect mechanism of the public’s WTP for healthy housing. This study acquires the following results: i) Information attentiveness to online reviews on different valence information of healthy housing as obtained in eye tracking experiments delivers significant effect on attitude, subjective norm (SN) and perceived behavioral control (PBC), but has no direct effect on the public’s WTP for healthy housing; ii) Hypotheses from TPB model are verified. attitude, PBC and SN can all make significant effect on WTP for healthy housing, with attitude showcasing the most prominent effect; and iii) In terms of the mediating effect, information attentiveness can deliver significant indirect effect on WTP through attitude.